2011
DOI: 10.4049/jimmunol.1001101
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitor LAQ824 Augments Inflammatory Responses in Macrophages through Transcriptional Regulation of IL-10

Abstract: Antigen-presenting cells (APCs) are important in the initiation of productive antigen-specific T-cell responses and in the induction of T-cell anergy. The inflammatory status of the APC at the time of encounter with antigen specific T-cells plays a central role in determining such divergent T-cell outcomes. A better understanding of the regulation of pro-inflammatory and anti-inflammatory genes in its natural setting, the chromatin substrate, might provide novel insights to overcome anergic mechanisms mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 51 publications
1
38
0
Order By: Relevance
“…Thus, low, nonapoptotic concentrations of the HDAC inhibitor ITF2357 reduce proinflammatory cytokine production in primary cells in vitro and exhibit antiinflammatory effects in vivo. In contrast, treatment of murine macrophages with the histone deacetylase inhibitor LAQ824 induced chromatin changes in the IL-10 gene promoter that results in recruitment of the transcriptional repressor HDAC11 (21). This result diminishes IL-10 production and induction of inflammatory cells.…”
Section: Continuedmentioning
confidence: 96%
“…Thus, low, nonapoptotic concentrations of the HDAC inhibitor ITF2357 reduce proinflammatory cytokine production in primary cells in vitro and exhibit antiinflammatory effects in vivo. In contrast, treatment of murine macrophages with the histone deacetylase inhibitor LAQ824 induced chromatin changes in the IL-10 gene promoter that results in recruitment of the transcriptional repressor HDAC11 (21). This result diminishes IL-10 production and induction of inflammatory cells.…”
Section: Continuedmentioning
confidence: 96%
“…Several US Food and Drug Administration (FDA)-approved small-molecule compounds inhibit the MERTK pathway although they were not originally developed for this purpose 190 . Myeloid cell functions are also regulated at the epigenetic level; as an example, drugs that interfere with chromatin remodelling, such as bromodomain and extra-terminal motif proteins 191,192 , or histone deacetylase (HDAC) inhibitors 193,194 , can affect inflammatory macro phage phenotypes. Other approaches to the modulation of macrophage functions include local low-dose ionizing radiation 146 and CD40 targeting, which can trigger macrophages to kill tumour cells 195 .…”
Section: Targeting Myeloid Cells To Limit Cancermentioning
confidence: 99%
“…Recently, we found that treatment of APCs with the pan-HDACi LAQ824 or LBH589 inhibits the production of the anti-inflammatory cytokine IL-10. This effect enabled the APCs to effectively prime naïve antigen-specific CD4 + T-cells and restore the responsiveness of tolerant T-cells isolated from tumor-bearing mice (28). These findings suggest that specific HDAC(s) likely participate in regulation of Il10 gene transcription and could be putative target(s) in the observed HDACi-mediated IL-10 inhibition.…”
Section: Introductionmentioning
confidence: 99%